Effects of Tree Spacing on the Physical and Mechanical Properties of 24-Year-Old Tectona grandis Wood in Longuza Forest Plantation, Tanzania - Samamba, Enos; Mwambusi, Japhet Noah; Chamshama, Shabani Athumani Omari (Jurnal Sylva Lestari, 2025)
This study investigated the effects of initial tree spacing on the physical and mechanical properties of 24-year-old teak (Tectona grandis) in Longuza Forest Plantation, Tanzania. Three spacing treatments (2 m × 2 m, 3 m × 3 m, and 4 m × 4 m) were evaluated using a randomized complete block design with three replications. Physical properties assessed included wood density (D) and heartwood percentage (HWP), while mechanical properties comprised modulus of elasticity (MOE), modulus of rupture (MOR), compressive strength parallel to the grain (CSP), shear strength parallel to the grain (SS), and cleavage strength (CLS). Results showed that spacing had no significant effect (p > 0.05) on most physical and mechanical properties, except for SS and tangential CLS at specific height levels. Although non-significant, D, MOE, MOR, CSP, and CLS tended to decrease with increasing spacing, whereas HWP and SS exhibited variable trends. The highest mean values for D (0.57 g/cm³), MOE (8,588 N/mm²), MOR (90.78 N/mm²), CSP (49.41 N/mm²), and CLS (14.83 N/mm) were observed at a 2 m × 2 m spacing, while the lowest values generally occurred at the widest spacing (4 m × 4 m). The findings suggest that closer spacing may enhance wood quality by promoting higher wood density and strength, although differences were not statistically significant. These results provide insights for silvicultural management of T. grandis plantations, suggesting that a 2 m × 2 m spacing may be preferable for optimizing physical and mechanical wood properties at older stand age. Keywords: heartwood percentage, modulus of elasticity, modulus of rupture, spacing, Tectona grandis, wood density